2007
DOI: 10.1097/01.sap.0000237637.65119.16
|View full text |Cite
|
Sign up to set email alerts
|

Acute Radial Artery Ischemia Following Therapeutic Steroid Injection

Abstract: Intra-arterial corticosteroid injection at the wrist can have devastating consequences. Anatomic arterial variation of the hand can lead to atypical presentation. A careful history and examination, with appropriate investigations, can lead to an accurate diagnosis in such difficult cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…One study described thirteen patients who developed 15 ruptured tendons subsequent to injection of a depository steroid in or around the tendons injected [44]. One study reported ischemia of the hand after carpal tunnel injection and one study after a corticosteroid injection for de Quervain tenosynovitis [45,46]. Nerve injury after steroid injection for carpal tunnel syndrome is described in 3 studies [47-49].…”
Section: Resultsmentioning
confidence: 99%
“…One study described thirteen patients who developed 15 ruptured tendons subsequent to injection of a depository steroid in or around the tendons injected [44]. One study reported ischemia of the hand after carpal tunnel injection and one study after a corticosteroid injection for de Quervain tenosynovitis [45,46]. Nerve injury after steroid injection for carpal tunnel syndrome is described in 3 studies [47-49].…”
Section: Resultsmentioning
confidence: 99%
“…No further intervention was needed, and the skin lesions fully healed within a week. Arterial embolization of steroids has been rarely reported, and in those cases, it was secondary to corticosteroid injection in the wrist ().…”
mentioning
confidence: 99%